Paraburkholderia phytofirmans PsJN triggers local and systemic transcriptional reprogramming in Arabidopsis thaliana and increases resistance against Botrytis cinerea - Nešić, Sofija; Bosnić, Dragana; Samardžić, Jelena; Nikolić, Ivana; Aziz, Aziz; Nikolić, Dragana (Frontiers in Plant Science, 2025)
Fungal pathogens are one of the main causes of yield losses in many crops, severely affecting agricultural production worldwide. Among the various approaches to alleviate this problem, beneficial microorganisms emerge as an environmentally friendly and sustainable alternative. In addition to direct biocontrol action against pathogens, certain plant growth-promoting bacteria (PGPB) enhance the plant immune defense to control diseases through induced systemic resistance (ISR). Paraburkholderia phytofirmans PsJN has been shown as an efficient biocontrol agent against diseases. However, the specific mechanisms underlying these beneficial effects at both local and systemic level remain largely unknown. In this study, we investigated the transcriptional response of Arabidopsis thaliana at above- and below-ground levels upon interaction with P. phytofirmans PsJN, and after Botrytis cinerea infection. Our data clearly support the protective effect of P. phytofirmans PsJN through ISR against B. cinerea in plants grown in both soil and hydroponic conditions. The comparative transcriptome analysis of the mRNA and miRNA sequences revealed that PsJN modulates the expression of genes involved in abiotic stress responses, microbe-plant interactions and ISR, with ethylene signaling pathway genes standing out. In roots, PsJN predominantly downregulated the expression of genes related to microbe perception, signaling and immune response, indicating that PsJN locally provoked attenuation of defense responses to facilitate and support colonization and the maintenance of mutualistic relationship. In leaves, the increased expression of defense-related genes prior to infection in combination with the protective effect of PsJN observed in later stages of infection suggests that bacterial inoculation primes plants for enhanced systemic immune response after subsequent pathogen attack.